Sosialisasi Laporan Keuangan UMKM dalam Rangka Membantu Program Kewirausahaan di Yayasan Al-Khoiriyah - Andry Sugeng; Neneng Hasanah; Dian Widiyati; Fitriyah Fitriyah; Agus Afandi (Abdimisi, 2020)
UMKM in South Tangerang must be able to support the improvement of the economic competitiveness of Banten Province, economic growth, poverty reduction, and improvement of the standard of living of the population in Banten Province. Therefore, UMKM must be able to compete and be able to seize every opportunity so that they can continue to take part in the national economy. This is because many UMKM is more focused on operational activities so that recording and reporting are often neglected. Without good records and reports, UMKM performance evaluation is not easy to do. The Al-khoiriyah Foundation has an entrepreneurship program for teenagers that aims to make their lives prosperous. In the program to create entrepreneurs at the Al-Khoiriyah Foundation, the participants were provided with knowledge and knowledge about the preparation of UMKM financial reports, limited human resources to recognize financial reports, and educational background were also reasons they had not been able to disseminate financial reports. The purpose of this community service is to provide socialization about entrepreneurship and compile MSME financial reports in theory and practice. The method used is seminars and direct delivery of the material as well as simulations and discussions on UMKM financial reports in entrepreneurship programs. This community service concludes that teenagers and foundation administrators who have been running businesses independently hope to be able to compile UMKM financial reports to determine the sustainability of their business and can be used as a condition for getting additional business capital for them.